Caveat emptor: what do we know about public administration evidence and how do we know it? - Isett, Kimberley R.; Vanlandingham, Gary; Head, Brian W. (2016)
This article provides an overview of a new feature in Public Administration Review called Evidence in Public Administration. This feature was created to provide a space in which scholars and practitioners of public administration can meet to engage in a dialogue about evidence in public decision making. In this feature, we will shine a light on the evidence needed to make effective decisions and examinations of the evidence that currently exists for contemporary public sector efforts. We explicitly want to create a resource for both practitioners and scholars to consult when trying to find evidence on a particular topic and to know the limitations and parameters of that evidence. This article lays out the purpose, scope, and rationale for the feature, as well as a call to engage in this endeavor. 11
Keywords: Public administration